Diagnostic meaning of digidrotestosterone levels in blood in men with idiopatic pathospermias - Мinuhin, A. S.; Коnоnеnkо, N. N. (Journal of Education, Health and Sport, 2017)
The experience of studying the levels of dehydrotestosterone in the blood of young men with pathospermia is given. It was established that its levels were significantly lowered in men with oligoasthenozoospermia in the background of androgenоdeficiency. It has been shown that the determination of the level of dihydrotestosterone and the testosterone-dihydrotestosterone ratio is of diagnostic significance in men with pathospermіаs.